PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DI LAZADA - Burong, Asnita Dewi Ina; Ridwan, Ridwan; Mannaga, Idham (Universitas Patria Artha, 2024)
This research aims to determine the effect of price on purchasing decisions. This research was carried out with an explanatory approach (explanatory research) which seeks to explain the influence of causality (causality relationship) and explain the influence of causality between the independent variable (price)and the dependent variable (purchase decision), the Lazada application in Palilolon village and the data was analyzed using simple linear regression analysis tool, using the Static Package For Social Science (SPSS 21) program. This type of research is based on the method using associative research through a quantitative approach. The population in the research were Lazada application customers in Palilolon village, totaling 200 people and a sample of 133 people. The sampling technique in this research ispurposive sampling, where the researcher takes samples with certain considerations. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis using a simple linear analysis method. The results of research based on this path analysis show that price has a significant effect on purchasing decisions